Influence of porcine intervertebral disc matrix on stem cell differentiation - Salzig, Denise; Schmiermund, Alexandra; Gebauer, Elke; Fuchsbauer, Hans-Lothar; Czermak, Peter (My University, 2011)
For back disorders, cell therapy is one approach for a real regeneration of a degenerated nucleus pulposus. Human mesenchymal stem cells (hMSC) could be differentiated into nucleus pulposus (NP)-like cells and used for cell therapy. Therefore it is necessary to find a suitable biocompatible matrix, which supports differentiation. It could be shown that a differentiation of hMSC in a microbial transglutaminase cross-linked gelatin matrix is possible, but resulted in a more chondrocyte-like cell type. The addition of porcine NP extract to the gelatin matrix caused a differentiation closer to the desired NP cell phenotype. This concludes that a hydrogel containing NP extract without any other supplements could be suitable for differentiation of hMSCs into NP cells. The NP extract itself can be cross-linked by transglutaminase to build a hydrogel free of NP atypical substrates. As shown by side-specific biotinylation, the NP extract contains molecules with free glutamine and lysine residues available for the transglutaminase.
Keywords: Nucleus pulposus extract; Gelatin; Mesenchymal stem cells; Transglutaminase